PERANCANGAN SISTEM INFORMASI PEMESANAN LAPANGAN FUTSAL BERBASIS WEB PADA CENTRO FUTSAL - Chandra Yuliansyah; Diwi Apriana; Nurfitri Andayani (Universitas Pahlawan Tuanku Tambusai, 2021)
The presentation of information on the availability of the futsal field which is still manual is one of the problems experienced by futsal field rental services because prospective tenants must come directly to the Futsal Center to find out the availability of the field. To make it easier for prospective tenants to access this system, the authors build a web-based futsal field ordering information system. The research design used is descriptive method and action method with Object Oriented Analysis and Design approach, the development method uses Prototype, the tool used to design the system is UML (Unified Modeling Language). This program is made using the PHP programming language, while the software chosen to design this application is Macromedia Dreamweaver 8 with XAMPP. With the existence of a web-based futsal field ordering information system, it is hoped that it can be useful for Centro Futsal in particular and outside Centro Futsal parties who need information about the Centro futsal field.